Aprendizagem de línguas em regime de tandem via e-mail: colaboração, autonomia e estratégias sociais e de compensação - Junia de Carvalho Fidelis Braga (2004)
This study aims to investigate the use of social and compensation learning strategies between students of Portuguese at California State University Fullerton and students of English at College English School participating in a Tandem e-mail program. The objective of the research is to identify the use of social and compensation strategies in the collaborative environment of Tandem via e-mail, identify traces of learner's autonomy in e-mail interactions and find out whether the virtual environment influences the development of the learner's linguistic skills and autonomy. This study is grounded on the social and compensation learning theories, on CALL-based theories, on collaborative learning theories, as well as on the theoretical assumptions ofthe construct ofautonomy. The methodology of this study is based on the qualitative paradigm. The interactions used in the 'Programa de Aprendizagem em Tandem Brasil e USA', which lasted for three months, make up the corpus ofthis study. In view ofthese assumptions and by means ofdata analysis, I demonstrate that the notions of bilingualism, reciprocity and autonomy are present in a tandem-based collaboration, that the use of learning strategies can help learners in the build-up of target language knowledge and that the virtual environment can promote linguistic development and learner's autonomy.